Experimental study for oxygen and nitrogen separation from air - Saw, Jeffry (Nanyang Technological University, 2024)
The proposed final year project (FYP) report seeks to address the gas separation phenomena using adsorption technology by utilising the pressure swing adsorption setup (PSA). The adsorption-based gas separation technique is used in food storage, air ventilation, and other applications. Highly concentrated or pure oxygen is a valuable resource utilised throughout a variety of industries such as the glass manufacturing industry, agriculture, chemical manufacturing, petrochemicals, power generation, oil and gas extraction, and refinery for petroleum. The main objective of this project is to determine the ideal conditions for producing oxygen gas with a purity of 85% or more. This will be accomplished by manipulating various variables, including the feed gas flow rate, feed gas pressure, pressurization duration, and adsorption time, within a Pressure Swing Adsorption (PSA) system. These adjustments are based on prior experimental data. The experiment was carried out using a 2-bed adsorption system that was furnished with essential components, including a Programmable Logic Controller (PLC) control panel, an oxygen analyser and electronic valves. Each variable was meticulously studied in isolation to determine its influence on both the PSA process and the purity of the generated oxygen gas. A PLC software is used to control a series of electronic valves (EVs) that open and close after a specific period, depending on the program settings. The timing of each adsorption/desorption process is determined by these controlled valves. After running the experiment a couple of times, I was able to obtain the optimal parameters for PSA to obtain the highest purity of Oxygen. The parameters are pressurization time of 0.3 seconds, feed gas pressure of 2.5 bar, feed flow rate angle of 90 degrees, adsorption time of 2.5 seconds and purge flow rate of 5.5 L/min. produced the highest purity amount in each of their experiment. Combining these parameters setting managed to improve O2 purity of 90%. The experiment was carried out for 20 minutes because the results no longer fluctuated after that period. The results of this study show that the zeolites employed are efficient at producing oxygen, with purity attaining above 85%. The ability to adsorb oxygen from air fulfils the project's goal of achieving greater than 85% purity using the most optimal settings. Recommendations were also provided for future researchers who aim to take on similar projects as this study, to assist them in their research.